Age-related morphometric characteristics of human skeletal muscle in male subjects - Kararizou, Evangelia; Manta, Panagiota; Kalfakis, Nikolaos; Vassilopoulos, Demetrios (Polish Journal of Pathology, 2009)
Objective: The purpose of the present study is to investigate the age-related changes in muscle biopsies from the quadriceps femoris in male subjects of different ages. Methods: A histological and histochemical study was performed on specimens from the quadriceps femoris from 8 males divided into two groups, under 50 and over 70 years of age. The following measurements were performed: a) number of type 1 and 2 fibres, b) diameter of type 1 and 2 fibres, c) percentage of the number and mean diameter of the two types in the interior and the peripheral area of fascicles. Results: The proportion of type 2 fibres decreased significantly with age (p < 0.005), especially in the periphery of the fascicles, but the proportion of type 1 fibres was not significantly changed. The correlation of fibre size with age showed that type 2 fibres decrease in size with age. This finding was more evident in the periphery of the fascicles (p < 0.05). Conclusion: We found that type 2 skeletal muscle fibres decreased in size and proportion with increasing age. The existence of these age changes should be taken into account in the interpretation of muscle biopsies of aged individuals.